Correlation Between Bioelectrical Impedance Analysis-Measured Body Fat, Body Mass Index and Waist Circumference with Cardiovascular Risk Factors in Acute Coronary Syndrome Patients - Imam Mahbub Zam Zami; Budi Susetyo Pikir (Universitas Airlangga, 2021)
Estimation of fat using bioelectrical impedance analysis (BIA) is thought to be a more predictive measure of cardiovascular (CV) risk assessment than body mass index (BMI) or waist circumference (WC). Percent body fat as measured using BIA (BIA-BF%) is independently associated with future cardiovascular events namely acute myocardial infarction, ischemic heart disease. This study is conducted to determine the correlation between body fat which consists of BIA-BF%, percentage of subcutaneous adipose tissue (SAT) and visceral fat level (Visceral Adipose Tissue/VAT) measured using BIA device, BMI and WC with CV risk factors (blood pressure, blood glucose level, LDL, HDL, TG, total cholesterol, HbA1c and serum fibrinogen) in patients with acute coronary syndrome (ACS). Material and Methods : This study used a cross-sectional correlation analysis. Sample was 70 ACS patients that match with inclusion criteria. Results : We found significant correlations between BIA-BF% with diastolic blood pressure, TG, and total cholesterol (r = 0.246, r = 0.250, r = 0.348 respectively; p <0.05). There was a significant correlation between VAT with diastolic blood pressure, LDL, TG, total cholesterol, HbA1c, and fibrinogen (r = 0.299, r = 0.306, r = 0.278, r = 0.265, r = 0.292, r = 0.330 respectively, p <0.05). There was a significant correlation between the percentage SAT and HDL levels (r = 0.318; p <0.05). We found no correlation between BMI and WC with blood pressure, LDL, HDL, TG, blood glucose, HbA1c and fibrinogen levels in ACS patients. Conclusion: VAT and BIA-BF% correlate with several cardiovascular risk factors better than BMI and WC. Body fat examination using BIA may be done to manage risk factors in ACS patients.